Designing an Artificial Intelligence–Based Digital Marketing Model in the ICT Industry - Karimnejad, Elmira; Rahiminik, Azam; Heidari, Seyed Abbas (Future of Work and Digital Management Journal, 2026)
The present study was conducted with the aim of designing an artificial intelligence–based digital marketing model in the ICT industry. The research adopted a mixed-methods design. In the qualitative phase, the statistical population consisted of executive managers in the ICT industry and university faculty members specializing in digital marketing. Within the executive group, individuals who were professionally active in the city of Tehran and had practical experience with digital marketing were considered. In the academic group, faculty members and digital marketing experts who possessed sufficient knowledge and experience in this field and had conducted relevant research were selected as members of the statistical population. To select participants for the qualitative phase from both executive managers and academic experts, purposive judgmental sampling and snowball sampling methods were employed. In the quantitative phase of the study, the model derived from the qualitative findings was empirically tested. The statistical population included employees, specialists, and managers of marketing units in companies operating in the national ICT industry, as well as digital marketing faculty members at leading universities in Tehran, with an estimated total population of approximately 900 individuals. Based on the Morgan table, a sample size of 269 participants was selected. The data collection instrument in this phase was a researcher-developed questionnaire grounded in the qualitative findings. The collected data were analyzed using SPSS and SmartPLS software packages. Initially, confirmatory factor analysis was conducted to assess construct validity and instrument reliability, followed by testing the proposed model using the structural equation modeling (SEM) approach. The results of the analyses indicated that the final model demonstrated an acceptable level of goodness of fit, and the relationships among the main variables were statistically significant and confirmed. Ultimately, the final artificial intelligence–based digital marketing model in the ICT industry comprised dimensions such as data-driven infrastructure, human capital empowerment, digital trust building, intelligent market adaptability, and marketing decision-making based on intelligent analysis of customer behavior, which can lead to improved efficiency, cost reduction, and enhanced effectiveness of marketing activities in this industry.